2021
DOI: 10.3233/faia210317
|View full text |Cite
|
Sign up to set email alerts
|

The Unreasonable Effectiveness of the Baseline: Discussing SVMs in Legal Text Classification

Abstract: We aim to highlight an interesting trend to contribute to the ongoing debate around advances within legal Natural Language Processing. Recently, the focus for most legal text classification tasks has shifted towards large pre-trained deep learning models such as BERT. In this paper, we show that a more traditional approach based on Support Vector Machine classifiers reaches competitive performance with deep learning models. We also highlight that error reduction obtained by using specialised BERT-based models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This means that for any given word in a text segment, its neighboring words to both the left and right are examined so that the context of the word is well understood. These representations lend themselves to high performance in text classification tasks when compared with traditional approaches using SVMs, for example [52,53]. We used the Simple Transformers software library [54] to deploy LMs.…”
Section: Methodsmentioning
confidence: 99%
“…This means that for any given word in a text segment, its neighboring words to both the left and right are examined so that the context of the word is well understood. These representations lend themselves to high performance in text classification tasks when compared with traditional approaches using SVMs, for example [52,53]. We used the Simple Transformers software library [54] to deploy LMs.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of large PLMs such as BERT (Devlin et al, 2018) has led to new SOTA performance in many NLP domains in recent years. In the legal domain, using domain-specific PLMs for simpler tasks such as text classification has only shown small improvements (Clavi'e and Alphonsus, 2021;Chalkidis et al, 2020). However, bigger gains were achieved for more complex tasks (Zheng et al, 2021).…”
Section: Logical Relations In Amrmentioning
confidence: 99%
“…2 However, the de facto interpretation of precedent in today's legal NLP landscape focuses only on positive outcomes. Several researchers have shown that a simple model can achieve very high performance for such formulation of the outcome prediction task (Aletras et al, 2016;Chalkidis et al, 2019;Clavié and Alphonsus, 2021;Chalkidis et al, 2021b), a finding that has been replicated for a number of jurisdictions .…”
Section: Introductionmentioning
confidence: 98%